The Effect of Free Shipping, Flash Sale, and COD on the Shopee Application on Student Consumptive Behavior - Rugu, Yolanda; Setyorini, Tuti (Journal of Practical Management Studies, 2024)
Shopee as one of the most popular online stores always provides promotions such as free shipping, flash sales, attractive prizes, and so on. Not only that, shopee also tries to provide convenience in transactions by providing various payment methods. One payment method that is considered practical and in demand by consumers is COD. Some consumers who have shopped and enjoy the benefits and convenience of shopping online on the shopee application tend to be addicted to online shopping, and eventually cause consumptive behavior. This study used an unknown number of Kupang State Polytechnic students. The sample taken amounted to 100 respondents with data collection techniques using questionnaires. This research uses instrument tests, classical assumption tests, and data analysis techniques, namely multiple linear analysis. The results of this study stated that free shipping and COD had a positive and significant influence on student consumptive behavior. Then flash sales have no influence and are not significant on student consumptive behavior. Free shipping, flash sale, COD simultaneously have a positive and significant effect on student consumptive behavior.